Local allergic rhinitis is an independent rhinitis phenotype: The results of a 10‐year follow‐up study. Issue 2 (15th September 2017) - Rondon, C.; Campo, P.; Eguiluz‐Gracia, I.; Plaza, C.; Bogas, G.; Galindo, P.; Mayorga, C.; Torres, M. J.
Abstract: Background: The knowledge about the natural history of local allergic rhinitis (LAR) is limited. One unmet question is to demonstrate whether LAR should be considered the first step in the development of allergic rhinitis (AR) or an independent phenotype. The aim of this study was to prospectively evaluate the natural history of a population with LAR, the potential conversion to AR with systemic atopy and the development of asthma during 10 years. Methods: This is the second phase of a 10‐year follow‐up study of a cohort of 176 patients with LAR of recent onset and 115 age‐ and sex‐matched healthy controls prospectively evaluated from 2005 to 2016. Clinical‐demographic questionnaire, spirometry, skin prick test and specific IgE were evaluated yearly. Nasal allergen provocation tests (NAPT) with Dermatophagoides pteronyssinus, Alternaria alternata, Olea europaea and grass pollen were performed at baseline, and after 5 and 10 years. Results: After 10‐year LAR, patients experienced a significant and clinically relevant worsening of the rhinitis, with increase in emergency assistance, development of asthma, loss of allergen tolerance and impairment of the quality of life. This worsening became significant after 5 years and progressed throughout 10 years. A similar rate of development of AR with systemic atopy was detected in patients and controls (9.7% vs 7.8%, log‐rank P =.623). In 5 patients, conversion to systemic atopy occurred >10 years (3%). Conclusions: LAR is a well‐differentiated clinical entity with a low rate of development of systemic atopy, a natural evolution towards worsening and a risk factor for suffering asthma.